Microbial metabolism of cannflavin A and B isolated from Cannabis sativa - Ibrahim, Amany K. (Phytochemistry, 2010)
Microbial metabolism of cannflavin A (1) and B (2), two biologically active flavonoids isolated from Cannabis sativa L., produced five metabolites (3–7). Incubation of 1 and 2 with Mucor ramannianus (ATCC 9628) and Beauveria bassiana (ATCC 13144), respectively, yielded 6″S,7″-dihydroxycannflavin A (3), 6″S,7″-dihydroxycannflavin A 7-sulfate (4) and 6″S,7″-dihydroxycannflavin A 4′-O-α-L-rhamnopyranoside (5), and cannflavin B 7-O-β-D-4‴-O-methylglucopyranoside (6) and cannflavin B 7-sulfate (7), respectively. All compounds were evaluated for antimicrobial and antiprotozoal activity.